Role of Communication Competence, Self-Control, and Professional Excellence in Enhancing the Performance of Academic Departmental Heads: An Evaluative Analysis - Saddiqa, Ayesha; Tariq, Shahnila; Mushtaq, Sidra (UMT Education Review, 2023)
A paramount element in the overall education process is the leadership of educational institutions. Communication, professional excellence, and self-control help the departmental heads to interact with communities, teachers and parents of students for the formation of character education. The current study investigated the relationship between professional excellence, self-control, and communication competence among the heads of academic departments. It was assumed that communication competence and self-control correlate with professional excellence. It was assumed that communication competence and self-control correlate with professional excellence. It was also assumed that Self-control is probable to predict professional excellence in academic departmental heads. Also, it was hypothesized that there is expected to be a difference in demographics and professional excellence in academic departmental heads. Purposive sampling technique and correlational research design were used to gather data from the academic heads. Self-Perceived Communication Competence Scale (SPCC), the Desirability of Control Scale, and the Professional Excellence Scale were used as measurement tools for present study. The results discovered a noteworthy correlation between communication competence and professional excellence. Also, a positive relationship was found between self-control and professional excellence, showing the importance of self control for the departmental heads. The findings can be used to implement a policy for the recruitment/ appointment of competent departmental heads, in order to maintain conducive working environment.